"Together we care" – bringing hospice and school communities together. Issue 2 (1st September 2011) - Bunce, Alison; Lee, Janice; Milligan, Stuart
Abstract : Introduction: Public education and health promotion are vital activities in every area of healthcare. The way society views death and dying can contribute to the experiences of people receiving end of life care and their carers. However both the End of Life Care Strategy and 'Living and Dying Well' highlight a lack of openness and discussion around death and dying. Both strategies call for national and local action to promote public awareness and challenge misconceptions. Ardgowan Hospice's 'Together We Care' schools project aims to dispel myths around and promote healthier responses towards death and dying. Aims/objectives: The project aims to bring together two different organisations serving our local community in an innovative and purposeful way. It will raise awareness within three school communities of the role Ardgowan Hospice plays, and will help children to be less anxious about discussing and contemplating death, dying and bereavement. Method: The project involves hospice staff: ▶ Developing innovative and purposeful relationships with our local schools ▶ Raising awareness of the role the hospice plays ▶ Bringing the hospice's key values to life through creative art projects ▶ Engaging with and enabling children to freely discuss any issues surrounding death, dying and loss. Results: The proposed poster will present data collected through the use of workbooks and evaluation forms. Discussion: Early evaluation results have shown that there is an increased awareness of the work of Ardgowan Hospice at all three schools, and that the first meeting with the classes involved was invaluable. The focus of activities to date has been on the hospice's key values. Conclusion: The project has enabled excellent relationships to be established. It is hoped that this kind of innovative and creative approach will begin to change attitudes to death, dying and loss in our local community.